Contextual uncertainty of visual scene modulates object-based attention. Issue 1 (January 2023) - Luo, Ting; Fu, Shimin
Contextual information involves invariant properties that are critical in selective attention. There is no direct evidence showing the effect of contextual information on object-based selective attention. The current study aimed to investigate the role of contextual uncertainty on object-based effect using a flanker task and to clarify the contradictory results obtained in previous studies. Herein, contextual uncertainty specifically referred to the configurations of the stimuli presented randomly as vertical or horizontal displays (high contextual uncertainty) that was reduced by showing consistent configurations within a block, via implicit learning of configuration (low contextual uncertainty). In Experiment 1, the object-based effect was observed under the high uncertainty condition and disappeared under the low uncertainty condition, demonstrating that contextual uncertainty modulated object-based attention. Experiment 2 provided explicit knowledge of the configural orientations, which can be utilised to sufficiently guide subsequent perception with increase in cueing interval, and therefore, affected contextual uncertainty. Relative to a short cueing interval, the long cueing interval enabled the participants to utilise the contextual knowledge for guiding visual attention and reducing uncertainty. Consistent with the finding in Experiment 1, the explicit manipulation of contextual uncertainty affected the object-based effect. The results proved that the contextual uncertainty played an important role in prioritisation in the object-based attentional selection. The mechanism of the interplay between contextual uncertainty and object-based attention was discussed.